THE EFFECT OF ECONOMIC INTEGRATION ON CREDIT CHANNEL: A CASE STUDY OF EURO ZONE - Durmuş Çağrı YILDIRIM (Fırat University, 2021)
Economic integration can changed the effectiveness of monetary policy on the real economy. For example European Monetary Union is an advanced stage of economic integration. The different financial architecture between European Monetary Union member countries undetermines the effects of policy implementation on the real economy. In the other words the changes in the common policy decisions of single supranational central bank for a group of countries that set up monetary union or full economic integration does not produce the desired results in national economies. Monetary transmission mechanism which is tried to explain the real effect of monetary policy changes on economy explains the effect process of the changes in monetary policy decisions of the policy makers in the general price level and output. This study focuses on the credit channel of monetary transmission mechanism. The aim of this study is to analyze the efficiency of bank credit channel of monetary transmission mechanism for 12 countries of European Monetary Union with the annual data for 2003-2010 periods. The analysis was conducted for Germany, Austria, Belgium, Finland, France, Netherlands, Ireland, Spain, Italy, Luxembourg, Portugal and Greece. As a result, it has been seen that policy interest rate has no significant effect on credit volume. As a result of the study it has been concluded that the bank credit channel has been lost it effectiveness in the review period. In addition, due to the crisis in the member countries the expansionary policies that was applied against crisis has an increasing effect on credit volume.